Efficacy and safety of a mobile app intervention in patients with inflammatory arthritis: a prospective pilot study : observational research - Fedkov, Dmytro; Berghofen, Andrea; Weiß, Christel; Peine, Christine; Lang, Felix; Knitza, Johannes; Kuhn, Sebastian; Krämer, Bernhard; Leipe, Jan (Rheumatology international, 2022)
EULAR highlighted the essential role of digital health in increasing self-management and improving clinical outcomes in patients with arthritis. The objective of this study was to evaluate the efficacy and safety of the digital health application (DHA) in patients with inflammatory arthritis. We assessed demographic parameters, treatment regimen, disease activity, and other patient-reported outcomes at baseline and after 4 weeks of DHA use added to standard care treatment. Of 17 patients, who completed the study, 7 (41.2%) patients were male, ranging from 19 to 63 (40.5 ± 12.2) years. No significant change in antirheumatic treatment was observed during the study. Statistically significant improvements (p < 0.05) were noted for health-related quality of life (increase in Physical Component Summary of Short Form-36 (SF-36) by 23.6%) and disease activity (decrease of Clinical Disease Activity Index and Simple Disease Activity Index by 38.4% and 39.9%, respectively). Clinically significant improvement was demonstrated for SF-36 Total Score (+ 14.4%), disease activity (Rheumatoid Arthritis Disease Activity Index− 5 to 15.9%), and depression (Patient Health Questionnaire− 9 to 13.5%). None of the efficacy parameters showed negative trends. No adverse events were reported throughout the study. The usability level was high i.e., the mean mHealth Application Usability Questionnaire Score of 5.96 (max.: 7.0) demonstrated a high level of application usability. This suggests that using a personalized disease management program based on DHA significantly improves several measures of patient-reported outcomes and disease activity in patients with inflammatory arthritis in a timely manner. These findings highlight the potential of complementary digital therapy in patients with inflammatory arthritis.